2004
DOI: 10.1128/jcm.42.2.665-669.2004
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Presence of Aspergillus Antibodies with Hemoptysis in Patients with Old Tuberculosis or Bronchiectasis but No Radiologically Visible Mycetoma

Abstract: Old tuberculosis and bronchiectasis are the two most important causes of chronic structural changes of lungs in our locality. In the absence of radiologically visible mycetoma, the cause of hemoptysis in these two groups of patients is largely unknown. A 17-month prospective study was carried out to compare the prevalence of Aspergillus fumigatus and Aspergillus flavus antibodies in hemoptysis patients with old tuberculosis or bronchiectasis but no radiologically visible mycetoma (cases, n ‫؍‬ 38), hemoptysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Pulmonary aspergillosis may manifest as cavities containing fungal balls referred to as mycetoma's or as chronic cavitatory or fibrosing aspergillosis [ 10 ]. Occurring in 7–11% of patients after previous PTB, the presence of both a mycetoma on radiological imaging (with CT demonstrating greater diagnostic accuracy than a standard chest x-ray [ 11 ]) as well as serum aspergillus antibodies leads to an increase incidence of clinically evident haemoptysis [ 12 ]. Erosion of adjacent vasculature and intra-cavitatory bleeding serve as the basis for haemoptysis in these patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary aspergillosis may manifest as cavities containing fungal balls referred to as mycetoma's or as chronic cavitatory or fibrosing aspergillosis [ 10 ]. Occurring in 7–11% of patients after previous PTB, the presence of both a mycetoma on radiological imaging (with CT demonstrating greater diagnostic accuracy than a standard chest x-ray [ 11 ]) as well as serum aspergillus antibodies leads to an increase incidence of clinically evident haemoptysis [ 12 ]. Erosion of adjacent vasculature and intra-cavitatory bleeding serve as the basis for haemoptysis in these patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CPA were the most likely among the three groups to receive antifungal treatment (CPA, 100.0% IPA, 80.4% PA, 48.4%), and the median treatment duration was also the longest (CPA, 176.5 days; IPA, 42.5 days; PA, 106.0 days), corroborating the slowly progressive course of CPA, which might improve with long-term antifungal treatment ( Table 1 ). 18 In contrast, nearly 20% of the patients with the more invasive IPA died before the diagnosis was suspected or shortly after treatment was started, and the less-invasive PA usually did not warrant treatment. In those who survived in the CPA group, a much shorter hospitalization duration for rehabilitation was usually required when compared with those who survived in the IPA group.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we showed that the mitochondrial genome of P. marneffei most closely related to that of A. nidulans, with the set of protein coding genes in the P. marneffei mitochondrial genome exactly the same as that in the A. nidulans mitochondrial genome, and except for the atp9 gene, the gene order of the protein genes is also the same as that in the A. nidulans mitochondrial genome [14]. Furthermore, their close relationships are also exemplified by the presence of unique antigenic proteins of the ''antigenic mannoprotein superfamily'' in P. marneffei and Aspergillus species [30][31][32][33][34][35][36][37][38][39], which have never been shown to be present in fungal species of other genera. In this study, all the genes in the putative sexual cycle of P. marneffei are found to be most closely related to their orthologues in Aspergillus species.…”
Section: Discussionmentioning
confidence: 97%